Pearl city - Vee, Julia; Bebelle, Ken (Vee, Julia. Phoenix hoard, 2025)
"Blade. Butcher. Thief. Worldbreaker. Emiko Soong has been called many things. But Worldbreaker is the worst. She unmasked the General and returned to San Francisco where her power is greatest. But the city, once her sanctuary from Jiaren intrigues, turns into her living nightmare. Clan wars erupt and Emiko's life becomes a treacherous quicksand of friend and foe. Unsure of who to trust, Emiko finds herself more alone than ever. When an ancient power rips through the Realm to land in her city, the General will stop at nothing to take it for his own. Emiko must face her past, present, and future, as she races to stop the General. Is Emiko's fate written to be the destroyer of worlds, or can she chart a new course to save her family? Phoenix Hoard #1 Ebony Gate #2 Blood Jade #3 Pearl City"--